Volleyball - Sheppard, J.; Charlton, P.; Watts, D.; Pelot, T. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Volleyball is amongst the most popular team sports worldwide, with reported participation rates ranking only second to soccer (Reeser et al., 2006). The sport is enjoyed at all competitive lev- els (junior, amateur, professional and Olympic) and since the inclusion of volleyball at the 1964 summer Olympic games in Tokyo, its popularity has continued to increase. According to the Federation International De Volley-Ball (HIVB) founded in 1947, the sport currently has over 200 member countries and approximately 150 million players participating (Bahr and Bahr, 1997). The worldwide popularity of volleyball is perhaps due, in part, to the minimal equipment requirements (only a net and ball) and non-contact nature of the game whereby opposing players are separated across a net, which lends itself to participation across genders and a variety of ages. Teams consist of six players per side, one setter, two middle blockers, one pass hitter and an opposite, in addition to recent rule changes denoting the inclusion of a defensive, non-jumping specialist - the Libero. The volleyball court is divided into front and back sections by the attack line (or three-metre line), with the majority of jump/landing activity (spiking, blocking and setting) occurring by the three players in the front court. Each time service is won back from the opposition, the players must rotate once by one position clockwise. Game rules stipulate the ball to be in rebound only, contrib- uting to ensuring the game is interesting and spectator friendly, as the ball is in constant motion. Volleyball rallies do not last long; in elite men`s volleyball most rallies last 5-12 seconds on average, but rallies can last up to 45 seconds. Typically, the rest time between playing rallies can range from 10-30 seconds. From a work/rest point of view, elite men`s indoor volleyball has a rest ratio range of 1:2.5-1.75:1. In addition to work/rest ratio, volleyball match length can range from 90-120 minutes. These demands result in high usage of the phosphagen and glycolytic energy systems and contributions from aerobic means to tolerate the repeated bouts and duration of a match. When developing metabolic conditioning programs for volleyball athletes during practises, work/rest ratios can be manipulated in game play. Work durations can be extended and rest periods controlled by `stacking` rallies of play through re-starting a rally immediately after or in specific duration after the cessation of the previous rally. This game play conditioning method has the additional benefit of skill and decision-making stress under fatigue, and is appropriately relevant for the players themselves. In addition, complementary metabolic conditioning can be achieved through general exer- cises. For example, skipping, sprinting, and medicine ball circuits can be designed to stress the metabolic and strength and power demands appropriate to volleyball. However, caution should be taken on general exercise selection for this population. For example, as volleyball athletes are generally tall and heavy, extensive running (i.e. jogging) tends to be a relative chronic injury risk. Furthermore, high volumes of cycling are likely a poor choice as the muscle architecture promoted by cycling athletes is disparate from that of non-cycling activity.